Cardiovascular benefits and safety of sotagliflozin in type 2 diabetes mellitus patients with heart failure or cardiovascular risk factors: a bayesian network meta-analysis - Li, Jiyifan; Zhu, Chenyang; Liang, Jingru; Hu, Jiarong; Liu, Haiyang; Wang, Zihan; Guan, Ruifang; Chow, Junwei; Yan, Shiwei; Li, Longzhou; Ma, Fuyan; Ma, Guo (Frontiers in Pharmacology, 2023)
Background: As an antidiabetic agent, sotagliflozin was recently approved for heart failure (HF). But its cardiovascular benefits in type 2 diabetic mellitus (T2DM) patients with HF or cardiovascular (CV) risk factors have not been systematically evaluated. The aim of this study is to evaluate the cardiovascular benefits and safety of sotagliflozin in T2DM patients with HF or CV risk factors using Bayesian network meta-analysis. Methods: Data were retrieved from PubMed, Embase, Web of Science, ClinicalTrials.gov and Cochrane Library from their inception to August 16th, 2023. Randomized controlled trials (RCTs) comparing sotagliflozin with placebo, dapagliflozin, and empagliflozin in adult T2DM patients with HF or CV risks for at least 12 weeks were included in the study. Data analysis was conducted using R 4.2.3 and Stata 17.0. Cardiovascular efficacy outcomes included HF events (hospitalization or urgent visits for HF), MACE (deaths from CV causes, hospitalizations for HF, nonfatal myocardial infarctions, and strokes), cardiovascular death, the decrease in SBP and weight loss. Safety outcomes are urinary tract infection, diarrhea, and diabetic ketoacidosis. Results: 11 studies with 30,952 patients were included. Compared to dapagliflozin and empagliflozin, 200 mg of sotagliflozin showed the best effect in reducing HF events (OR [95% CI], 0.79 [0.66, 0.94] and 0.90 [0.63, 1.27]). Compared to dapagliflozin, 200 mg of sotagliflozin (OR [95% CI], 0.76 [0.66, 0.87]) was superior in preventing MACE. Compared to empagliflozin, 200 mg of sotagliflozin (OR [95% CI], 1.46 [1.04, 2.05]) was inferior in preventing CV death. Sotagliflozin showed poorer SBP decreasing effect than empagliflozin and dapagliflozin (MD [95% CI], 1.30 [0.03, 2.56] and 2.25 [0.35, 4.14], respectively). There was no significant difference between sotagliflozin and other interventions in weight loss. Sotagliflozin exhibited no increased risk for diabetic ketoacidosis or urinary tract infection among all interventions, however, it showed mild risk for diarrhea than placebo (OR [95% CI], 1.47 [1.28, 1.69]). Conclusion: Sotagliflozin displayed moderate CV benefits and acceptable safety. Sotagliflozin can be one of the recommended options for T2DM patients with HF or CV risk factors, which will be important for evidence-based use of sotagliflozin as well as decision-making of T2DM medication.